1989
DOI: 10.1093/brain/112.4.1039
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Typical Absence Seizures in Epileptic Syndromes

Abstract: This is a comparative video-electroencephalographic (EEG) study of typical absence seizures in 4 epileptic syndromes. In 20 patients, 224 absences were recorded and analysed. Significant clinical and EEG differences were found in the seizure patterns of childhood absence epilepsy (CAE), juvenile absence epilepsy (JAE), juvenile myoclonic epilepsy with absences (JMEA) and myoclonic absence epilepsy (MAE). Clinically, CAE demonstrated more severe impairment of consciousness than JAE while, in JMEA, ictal manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
3
10

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 11 publications
7
104
3
10
Order By: Relevance
“…Segundo o estudo de Panayiotoupolos e col. 4 , as crises de ausência típica podem ser descritas pelo paciente como "blackouts", "obnubilação" ou "fuga de pensamento". De acordo com o subtipo de epilepsia (ausência infantil, juvenil e ausência da EMJ) há um padrão eletrográfico típico.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Segundo o estudo de Panayiotoupolos e col. 4 , as crises de ausência típica podem ser descritas pelo paciente como "blackouts", "obnubilação" ou "fuga de pensamento". De acordo com o subtipo de epilepsia (ausência infantil, juvenil e ausência da EMJ) há um padrão eletrográfico típico.…”
Section: Discussionunclassified
“…De acordo com o subtipo de epilepsia (ausência infantil, juvenil e ausência da EMJ) há um padrão eletrográfico típico. As crises de ausência da EMJ geralmente são de curta duração e pouco frequentes, ao contrário das ausências infantil e juvenil, que são mais prolongadas 4 . Somente um paciente (Paciente 2) (4 %) do grupo com o diagnóstico de EMJ apresentou convulsão febril na infância.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pyknolepsy would be characteristic of CAE and spaniolepsy of JAE. For Panayiotopoulos, pyknolepsy would not be patognomonic of CAE and could occur in JAE, although less frequently 16,17 . In the present study when we utilized his criteria we observed pyknolepsy in all patients with CAE and in 64.2% of those with JAE.…”
Section: Eeg Exclusion Criteriamentioning
confidence: 99%
“…We previously showed that typical absences are not one symptom but a cluster of clinical EEG manifestations that are syndrome related (17)(18)(19)(20)(21). This may also be the case in absence status, the manifestations of which and its relations to the various syndromes of IGEs are not known.…”
mentioning
confidence: 99%